The Sustainable MBA : a Business Guide to Sustainability. - Weybrecht, Giselle (Wiley, 2013)
Whether you are an employee, a manager, an entrepreneur or a CEO, The Sustainable MBA Second Edition provides the knowledge and tools to help you 'green' your job and organization, to turn sustainability talk into action for the benefit of your bottom line and society as a whole. Based on more than 150 interviews with experts in business, international organizations, NGOs and universities from around the world, this book brings together all the pieces of the business and sustainability puzzle including: What sustainability is, why you should be interested, how to get.